Formulation and Characterization of Clotrimazole Loaded Polymeric Nanoparticles Fabricated by Single Emulsion Evaporation Technique - Viswanath, Valikala; Krishna, Palla Venkata Murali; Babu, Vankam Lokeswara; Lakkamma, Tanuja Anajigere Mruthunjaya (Indian Journal of Pharmaceutical Education and Research)
Aim/background: Utilizing nanotechnology allows us to shrink machinery down to the atomic level, leading to groundbreaking progress in technical innovation. Our most recent efforts concentrated on developing polymeric nanoparticles loaded with clotrimazole to investigate their antifungal abilities. Materials and Methods: Polymeric nanoparticles were synthesized by blending aqueous polyvinyl alcohol with methanolic polycaprolactone and clotrimazole in various ratios. The mixture underwent high-speed homogenization, ultrasonication, and magnetic stirring to facilitate the formation and recovery of the nanoparticles. Results: FTIR analysis confirmed the presence of essential functional groups and ruled out drug-excipient incompatibilities. Particle size measurements ranged from 80.24±0.03 to 142.18±0.06 nm, with a zeta potential between -21.9 mV and -13.2 mV. SEM and TEM images revealed that particles were uniformly sized below 50 nm, though occasional aggregation was observed. AFM and XRD studies revealed the crystalline nature of nanoparticles with an average diameter of 25±10 nm and a height of 40±15 nm. The antifungal investigations demonstrated substantial antifungal efficacy against resistant C. glabrata and C. albicans strains, with MIC values of 25.3±0.4 and 23.2±0.3, and IC50 values of 273.3±2.8 and 362.2±0.4, respectively. Conclusion: The study developed clotrimazole-loaded polymeric nanoparticles with optimized size, shape and zeta potential for effective membrane penetration and stability. Comprehensive spectroscopic, microscopic, and thermal analyses confirmed that the nanoparticles were spherical, pure, and crystalline with strong antifungal activity against resistant C. glabrata and C. albicans, suggesting promising potential potential for future commercial use.
Keywords: Nanoparticles; Nanosystems; Nanocarriers; Nanomaterials; Nanostrutures and Clotrimazole.